Grafos destinados al Análisis de datos Multivariante Condicionado por su Estructura - García Montoya, Miguel Angel (2000)
We present two new methods for the construction of graphs that can be used with descriptive techniques of Multivariate Data Analysis: a graph based in the chi-square distance and a graph based in strongly-connected components. We also present exemples corresponding to the graphs, using data from an intermediate Input-Output Matrix.